2016
DOI: 10.1002/adma.201604381
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Gold Nanorod@Metal–Organic Framework Nanoprobes for Multimodality Diagnosis of Glioma

Abstract: One of the most significant challenges in the diagnosis of brain cancer is efficient in vivo imaging using nontoxic nanoprobes. Core-shell gold nanorod@MIL-88(Fe) nanostars are successfully constructed as triple-modality imaging (computed tomography/magnetic-resonance imaging/photoacoustic imaging) nanoprobes that show low cytotoxicity, high contrast, high penetration depth, and high spatial resolution for accurate and noninvasive imaging and diagnosis of gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 36 publications
0
134
0
Order By: Relevance
“…Integrating the advantages of CT, MRI, and PAI into one, Tian and co-workers structured a core-shell NMOFs nanoprobe based on PEG-decorated Au nanorods and MIL-88(Fe) for high, enhanced CT, MRI, and PAI imaging of glioma in vivo (Figure 7a). [52] The results showed that the nanoprobe concentrations and the signal intensities of CT, MRI, and PAI exhibited positive linear relationships within a certain range. Notably, Au@MIL-88(Fe) with low cytotoxicity provided high contrast in CT, MRI, and PAI (Figure 7b), which significantly improved imaging sensitivity, high penetration depth, and spatial resolution of glioma imaging in vivo, providing opportunities for advanced multimodal imaging applications of tumors from preclinical to clinical research.…”
Section: Multimodal Bioimagingmentioning
confidence: 91%
See 3 more Smart Citations
“…Integrating the advantages of CT, MRI, and PAI into one, Tian and co-workers structured a core-shell NMOFs nanoprobe based on PEG-decorated Au nanorods and MIL-88(Fe) for high, enhanced CT, MRI, and PAI imaging of glioma in vivo (Figure 7a). [52] The results showed that the nanoprobe concentrations and the signal intensities of CT, MRI, and PAI exhibited positive linear relationships within a certain range. Notably, Au@MIL-88(Fe) with low cytotoxicity provided high contrast in CT, MRI, and PAI (Figure 7b), which significantly improved imaging sensitivity, high penetration depth, and spatial resolution of glioma imaging in vivo, providing opportunities for advanced multimodal imaging applications of tumors from preclinical to clinical research.…”
Section: Multimodal Bioimagingmentioning
confidence: 91%
“…b) CT (b1,2), MRI (b3,4), and PAI (b5,6) images of U87 MG‐bearing mice before and after intravenous injection with Au@MIL‐88(Fe) nanoplatform. Reproduced with permission 52. Copyright 2016, Wiley‐VCH.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 94%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) has the characteristics of safe, noninvasive, high spatial resolution, multi‐azimuth, and multi‐parameter imaging 1,2. At the same time, the obtained anatomical information is not affected by tissue depth 3,4. In clinical diagnosis today, MRI is rated among the very significant imaging modalities 5,6.…”
Section: Introductionmentioning
confidence: 99%